2008
DOI: 10.1002/jmri.21484
|View full text |Cite
|
Sign up to set email alerts
|

High‐spatial‐resolution three‐dimensional MR cholangiography using a high‐sampling‐efficiency technique (SPACE) at 3T: Comparison with the conventional constant flip angle sequence in healthy volunteers

Abstract: Purpose:To evaluate the image quality of high-spatialresolution three-dimensional magnetic resonance cholangiography (MRC) with a high-sampling-efficiency technique (sampling perfection with application optimized contrasts using different flip angle evolutions [SPACE]) in comparison with a conventional constant flip angle (FA) sequence at 3T. Materials and Methods:Eighteen volunteers were examined on a 3T MR unit using MRC imaging performed with three different free-breathing three-dimensional T2-weighted turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…The most common clinical fi nding in B-cell lymphoma of the breast is a painless palpable mass, less frequently associated with retraction of the nipple [2,7,8]. Skin changes or edema, on the other hand, have been reported to occur more often in T-cell breast lymphoma [4,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common clinical fi nding in B-cell lymphoma of the breast is a painless palpable mass, less frequently associated with retraction of the nipple [2,7,8]. Skin changes or edema, on the other hand, have been reported to occur more often in T-cell breast lymphoma [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Skin changes or edema, on the other hand, have been reported to occur more often in T-cell breast lymphoma [4,9]. Similarly, image fi ndings have been described as non-specifi c with a broad variety of features leaving an uncertainty to distinguish between breast carcinoma or hematological malignancy [2,4,7,8,[10][11][12]. Due to its rare occurrence and its non-specifi c fi ndings, these ambiguities can lead to misinterpretations of clinical and radiological features which may result in a delayed or inaccurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Three-tesla MR imaging has recently been attempted as well using 3D MRCP with SPACE (sampling perfection with application optimized contrasts using diŠerent ‰ip angle evolutions) sequence. 8,9 This reduces speciˆc absorption rate (SAR) for 3.0T imaging by using a variable ‰ip angle and reduces acquisition time when combined with the GRAPPA (generalized autocalibrating partially parallel acquisition) reconstruction algorithm. It also reduces echo spacing, an advantage not previously explored.…”
Section: Introductionmentioning
confidence: 99%
“…It has been already reported superior to conventional 3D TSE MRCP at 3.0T. 9 At 3.0T, it is necessary to reduce the ‰ip angle or use a variable ‰ip angle to limit the SAR, 9 whereas at 1.5T, the SAR causes less disturbance, thus negating the need to use a variable ‰ip angle. In addition, short echo time (TE), which can be produced by varying ‰ip angle in 3.0T MR imaging, is not an original requirement for MRCP.…”
Section: Introductionmentioning
confidence: 99%
“…The development of respiratory-triggered three-dimensional (3D) T2-weighted (T2W) turbo spin echo (TSE) techniques made MRCP highly useful [3] and a new technique, sampling perfection with the application of optimized contrasts using different flip angle evolutions (SPACE) improved the image quality of MRCP scans [4][5][6]. At 1.5 T unit, it is reported that navigator-gated MRCP with a balanced turbo-field-echo (BTFE) sequence is more useful than conventional respiratorytriggered MRCP with a heavily T2W sequence for evaluating the gallbladder and cystic duct in patients scheduled for laparoscopic cholecystectomy because the former reduces motion artifacts due to irregular breathing and clearly shows concentrated or hemorrhagic bile whose detection is difficult on TSE sequences [7,8].…”
mentioning
confidence: 99%